Nutritional Status Deterioration Occurs Frequently During Children’s ICU Stay* - Frédéric V. Valla; Florent Baudin; Bénédicte Gaillard Le Roux; Carole Ford‐Chessel; Elodie Gervet; Céline Giraud; Tiphanie Ginhoux; Fleur Cour‐Andlauer; Étienne Javouhey; Lyvonne N. Tume (2019)
Malnutrition and faltering growth at PICU admission have been related to suboptimal outcomes. However, little is known about nutritional status deterioration during PICU stay, as critical illness is characterized by a profound and complex metabolism shift, which affects energy requirements and protein turnover. We aim to describe faltering growth occurrence during PICU stay.Single-center prospective observational study.Twenty-three-bed general PICU, Lyon, France.All critically ill children 0-18 years old with length of stay longer than 5 days were included (September 2013-December 2015).Weight and height/length were measured at admission, and weight was monitored during PICU stay, in order to calculate body mass index for age z score. Faltering growth was defined as body mass index z score decline over PICU stay. Children admitted during the first year of the study and who presented with faltering growth were followed after PICU discharge for 3 months.We analyzed 579 admissions. Of them, 10.2% presented a body mass index z score decline greater than 1 SD and 27.8% greater than 0.5. Admission severity risk scores and prolonged PICU stay accounted for 4% of the variability in nutritional status deterioration. Follow-up of post-PICU discharge nutritional status showed recovery within 3 months in most patients.Nutritional deterioration is frequent and often intense in critically ill children with length of stay greater than 5 days. Future research should focus on how targeted nutritional therapies can minimize PICU faltering growth and improve post-PICU rehabilitation.